High urinary excretion of glycosaminoglycans: a possible marker of glomerular involvement in diabetes - Gambaro, G; Cicerello, E; Mastrosimone, S; Lavagnini, T; Baggio, B (Metabolism, clinical and experimental, 1989)
Many insulin-dependent diabetic patients with albuminuria in the "not at risk range" for diabetic nephropathy present high urinary excretion rates of glycosaminoglycans. A lysine provocative test in these subjects disclosed abnormal urinary excretion of albumin, unlike findings obtained in insulin-dependent diabetic patients with normal urinary excretion rates of glycosaminoglycans. These data support the hypothesis that high urinary excretion of glycosaminoglycans is a marker of glomerular involvement in diabetes mellitus.